Auto Power Management System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a day’s efficient energy utilization is the utmost priority in many industries so as to minimize the energy cost.  This paper aims to deliver the techniques involved in the control of load in industry during heavy traffic with the help of Programmable logic controller (PLC). It also explains the usage of to monitor all the load parameters of the motor on personal computer. In the considered paper we have implemented the multifunction meter (MFM) to PLC communication with Modbus Remote Terminal Unit (RTU) communication; direct values from MFM are taken as feedback to the PLC. Initially constant current values to a single load is taken into the consideration, and any higher load is being applied on the current load, the variations in amps rating is taken as reference and extra load gets tripped at the same time power is managed. With the help of energy meter voltage and amperes rating is constantly observed, if variations of loads are observed rather than any pre defined load, alarms occurs in Supervisory Control And Data Acquisition (SCADA) and power and energy gets managed.